Strategi Pengembangan Bisnis Kafe dengan Metode SWOT dan QSPM - Ningsih, Margie Subahagia; Sikumbang, Raja Irhas; Rida, Rizkha; Fitri, Li Idi’il (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Rajin Djalan wants to be more successful and competitive in the coffee shop business in Medan. This study aims to find the best business development strategy for Rajin Djalan in facing competition. Business development strategies are formulated based on SWOT and QSPM analysis. Alternative strategies undertaken for business development should prioritize strategy 2, namely by utilizing social media and creating content that is relevant to consumers and attractive. Results from the SWOT analysis, so the right business development strategy for Rajin Djalan is the S-O (Strengths - Opportunities) strategy, namely using strengths to take advantage of opportunities with alternative strategies: a. Endorsement by Influencer b. Utilize social media and create content that is relevant to consumers and interesting.